Unfolding the possibility to develop share-waqf in Indonesia through the concepts, opportunities & challenges - Aldi Khusmufa Nur Iman; Faridatun Najiyah; Munji Asshiddiqi (Journal of Islamic Economic Laws, 2021)
Indonesia is a country with the largest Muslim population in the world. The potential of Islamic financial instruments for the welfare of the people grows in society, one of which is cash waqf and shares. Most Islamic scholars allow cash and shares to be used as objects of waqf. Both cash and stock endowments can be implemented into two models. Cash waqf can be implemented as mutual funds or converted into other fixed assets. Meanwhile, the implementation of share waqf can be done through corporate waqf and individual share waqf. Individual share waqf is applied with two models, namely waqf from the profit of shares and waqf in the form of per-lot Sharia shares. The purpose of this study is to determine the concepts, opportunities and challenges of share waqf in Indonesia. Based on the research, it was found that share waqf has a great opportunity in Indonesia, considering that the majority of the population is Muslim. However, the implementation of the share waqf program in Indonesia in the future face various challenges that must be resolved in order for the share waqf to develop in Indonesia.